2008
DOI: 10.1136/hrt.2007.139683
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic implications of dipyridamole stress cardiovascular magnetic resonance on the basis of the ischaemic cascade

Abstract: Dypiridamole stress CMR is able to stratify risk on the basis of the ischaemic cascade. A small group of patients with severe ischaemia-simultaneous perfusion deficit and inducible wall motion abnormalities-are at the highest risk and benefit most from MACE reduction due to revascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 25 publications
(33 reference statements)
0
33
0
Order By: Relevance
“…2. Eventually, 11 studies [5,6,8,[18][19][20][21][22][23][24][25] fulfilled all inclusion criteria and were eligible for meta-analysis. All eligible studies had been published in peer-reviewed journals between 2004 and 2011.…”
Section: Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2. Eventually, 11 studies [5,6,8,[18][19][20][21][22][23][24][25] fulfilled all inclusion criteria and were eligible for meta-analysis. All eligible studies had been published in peer-reviewed journals between 2004 and 2011.…”
Section: Search Resultsmentioning
confidence: 99%
“…For prognostic utility, six studies evaluated stress cine MRI [5,6,8,19,[21][22] and seven studies evaluated stress p-MRI [6,18,20,[22][23][24][25]. Three studies evaluated both stress cine MRI and stress p-MRI in the same patient groups [6,21,22]. Five studies reported data on both hard cardiac events and MACE [5,6,8,18,23], three studies hard cardiac events only [19,22,24], and three studies MACE only [20,21,25].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations